Relationship between non-ionizing radiation (NIR) exposure level and the base station tower installation around Kuala Nerus - A.R.S.N, Dianah; S.N, Hazmin; H.N, Syafiqah; M.K.A, Kamarudin; R, Umar (2018)
The rapid development of wireless technology nowadays has led to the increases of erection of base station telecommunication (BST). However, the exposure transmitted from BST generated the public concern on health problem because it is said can causes high risk to the human and surroundings. Therefore, this study will focused on the influence of selected BST installed around Kuala Nerus towards the ambient NIR exposure value at surroundings. By using spectrum analyzer connected to receiving omni-directional antenna, the NIR exposure level in terms of electric field (EF) strength is measured horizontally at 50 m until 500 m around the BSTs. The comparison between the measured values and the international reference levels of ICNIRP were done. Besides, the exposure values were compared among the BSTs area by considering the other influenced factors at surroundings. The result shows that the highest exposure level was recorded at BST located in sub-urban area and has the higher number of antennas installed on the top. It can be concluded that the number of BST nearby, the number of antennas, the direction of the antenna and the presence of other sources influenced the ambient NIR exposure at that area.